DNA Damage prevention by the use of Computational Designed Microlpastics adsorbing Chemicals. - Khadija Abbas Sahan; Zahraa Abbas Sahan (Baghdad Journal of Biochemistry and Applied Biological Sciences, 2025)
Cancer development is driven by uncontrolled cellular proliferation resulting from the accumulation of genetic mutations. One of the most well-studied mechanisms behind these mutations is DNA damage. Cellular DNA is under constant threat of damage by exogenous and endogenous sources. Microplastics are one of these exogenous sources and characterized by their small size and high surface-area-to-volume ratio, have the ability to interact strongly with biological systems, leading to cytotoxicity, cell damage, and DNA mutations that increase cancer risk. Microplastics uptake and subsequent bioaccumulation in the human body are increasingly considered to negatively impact the body’s usual mechanisms of damage repair, with resultant increases in apoptosis, necrosis, inflammation, oxidative stress, and aberrant immune responses. In this study we tried to Design a compound for the efficient absorption of microplastics by the use of PubChem, Avogadro, PyMOL, and SWISSADME. A general approach to designing such a compound include: 1. Targeting and Binding Microplastics. 2. Biocompatibility. 3. Efficient Elimination. 4. Delivery Mechanism. We found that modified chitosan could be the best compounds for microplastics adsorption from human body. PubChem was used to obtain the Chitosan chemical structure (C56H103N9O39) M.wt: 1526.5 g/mol. Avogadro was used for Chitosan fragmentation in to smaller pieces to increase solubility, permeability through cellular membrane and enhance activity. PyMOL was used to check out the 3D structure and its functional groups. SWISSADME was applied to analyze GI absorption, skin permeation, bioavailability, and the level of compliance with Lipinski rules of 5. This research highlights the potential of chitosan-based compounds as a prevention strategy for mitigating microplastic-induced carcinogenesis.